Exhumation history of the Peake and Denison Inliers: insights from low-temperature thermochronology. Issue 7 (2nd October 2016) - Hall, J. W.; Glorie, S.; Collins, A. S.; Reid, A.; Evans, N.; McInnes, B.; Foden, J.
ABSTRACT: Multi-method thermochronology applied to the Peake and Denison Inliers (northern South Australia) reveals multiple low-temperature thermal events. Apatite fission track (AFT) data suggest two main time periods of basement cooling and/or reheating into AFT closure temperatures (∼60–120°C); at ca 470–440 Ma and ca 340–300 Ma. We interpret the Ordovician pulse of rapid basement cooling as a result of post-orogenic cooling after the Delamerian Orogeny, followed by deformation related to the start of the Alice Springs Orogeny and orocline formation relating to the Benambran Orogeny. This is supported by a titanite U/Pb age of 479 ± 7 Ma. Our thermal history models indicate that subsequent denudation and sedimentary burial during the Devonian brought the basement rocks back to zircon U–Th–Sm/He (ZHe) closure temperatures (∼200–150°C). This period was followed by a renewal of rapid cooling during the Carboniferous, likely as the result of the final pulses of the Alice Springs Orogeny, which exhumed the inlier to ambient surface temperatures. This thermal event is supported by the presence of the Mount Margaret erosion surface, which indicates that the inlier was exposed at the surface during the early Permian. During the Late Triassic–Early Jurassic, the inlier was subjected to minor reheating to AFT closure temperatures; however, the exact timing cannot be deduced from our dataset. Cretaceous apatite U–Th–Sm/He (AHe) ages coupled with the presence of contemporaneous coarse-grained terrigenous rocks suggest a temporally thermal perturbation related with shallow burial during this time, before late Cretaceous exhumation cooled the inliers back to ambient surface temperatures.